The combined influence of task accuracy and pace on motor variability in a standardised repetitive precision task - Srinivasan, D.; Mathiassen, Svend; Samani, A.; Madeleine, P. (Taylor & Francis, 2015)
© 2015 Taylor & Francis. Thirty-five healthy women, experienced in pipetting, each performed four pipetting sessions at different pace and accuracy levels relevant to occupational tasks. The size and structure of motor variability of shoulder and elbow joint angles were quantified using cycle-to-cycle standard deviations of several kinematics properties, and indices based on sample entropy and recurrence quantification analysis. Decreasing accuracy demands increased both the size and structure of motor variability. However, when simultaneously lowering the accuracy demand and increasing pace, motor variability decreased to values comparable to those found when pace alone was increased without changing accuracy. Thus, motor variability showed some speed-accuracy trade-off, but the pace effect dominated the accuracy effect. Hence, this trade-off was different from that described for end-point performance by Fitts' law. The combined effect of accuracy and pace and the resultant decrease in motor variability are important to consider when designing sustainable work systems comprising repetitive precision tasks.